Steroidal scaffolds as FXR and GPBAR1 ligands: from chemistry to therapeutical application. (July 2015) - Sepe, Valentina; Distrutti, Eleonora; Limongelli, Vittorio; Fiorucci, Stefano; Zampella, Angela
Bile acids (BAs) are experiencing a new life. Next to their ancestral roles in lipid digestion and solubilization, BAs are today recognized signaling molecules involved in many physiological functions. These signaling pathways involve the activation of metabolic nuclear receptors, mainly the BA sensor FXR, and the dedicated membrane G protein-coupled receptor, GPBAR1 (TGR5). As a consequence, the discovery of GPBAR1/FXR selective or dual modulators represents an important answer to the urgent demand of new pharmacological opportunity for several human diseases including dyslipidemia, cholestasis, nonalcoholic steatohepatitis, Type 2 diabetes and inflammation. Targeted oriented discovery of natural compounds and medicinal chemistry manipulation have allowed the development of promising drug candidates.